Adrenal gland plasticity in lactating rats and mice is sufficient to maintain basal hypersecretion of corticosterone. (4th May 2017) - Perani, Clara V.; Langgartner, Dominik; Uschold-Schmidt, Nicole; Füchsl, Andrea M.; Neumann, Inga D.; Reber, Stefan O.; Slattery, David A.
Abstract: Increased basal glucocorticoid secretion and a reduced glucocorticoid response during acute stress, despite only minor changes in the secretion of the major secretagogue adrenocorticotropic hormone (ACTH), have been documented in the peripartum period in several species. We recently showed that the adrenal gland, the site of glucocorticoid synthesis, undergoes substantial postpartum-associated plasticity in the rat at mid-lactation. Here, we asked the question whether adrenal changes already take place around parturition in the rat and in another species, namely the mouse. After demonstrating that several components of the adrenal machinery mediating cholesterol supply for steroidogenesis, including protein levels of hormone-sensitive lipase, low-density lipoprotein receptor (LDLR) and scavenger receptor class-B type-1 (SRB1), are upregulated, while hydroxymethylglutaryl coenzyme A reductase (HMGCR) is downregulated in the lactating rat one day after delivery, as previously observed at mid-lactation, we demonstrated profound changes in the mouse. In detail, protein expression of LDLR, SRB1, HMGCR and adrenal lipid store density were increased in the mouse adrenal one day after parturition as tested via western blot analysis and oil-red lipid staining, respectively. Moreover, using in vitro culture techniques, we observed that isolated adrenal explants from lactating mice secreted higher levels of corticosterone under basal conditions, but showed impaired responsiveness to ACTH, mimicking the in vivo scenario. These results suggest that mechanisms of adaptation in the maternal adrenal after delivery, namely increased cholesterol availability and decreased ACTH sensitivity, are crucial for the basal increase in circulating glucocorticoids and maternal stress hyporesponsiveness that are typical of this period.